Homogenized models for a short-time filtration in elastic porous media - Anvarbek M. Meirmanov (Electronic Journal of Differential Equations, 2008)
We consider a linear system of differential equations describing a joint motion of elastic porous body and fluid occupying porous space. The rigorous justification, under various conditions imposed on physical parameters, is fulfilled for homogenization procedures as the dimensionless size of the pores tends to zero, while the porous body is geometrically periodic and a characteristic time of processes is small enough. Such kind of models may describe, for example, hydraulic fracturing or acoustic or seismic waves propagation. As the results, we derive homogenized equations involving non-isotropic Stokes system for fluid velocity coupled with two different types of acoustic equations for the solid component, depending on ratios between physical parameters, or non-isotropic Stokes system for one-velocity continuum. The proofs are based on Nguetseng's two-scale convergence method of homogenization in periodic structures.